MEMBERS' PERCEPTIONS ON THE FUNCTIONS OF FARMER GROUP IN RICE RICE FARMING BUSINESS IN SYAMTALIRA ARON DISTRICT, UTARA ACEH REGENCY - Irmawati Irmawati; Setia Budi; Afni Zahara (LPPM Universitas Malikussaleh - Indonesia, 2022)
The farmer group is a farme entity that directly organizes the function of farme in deloving their farming. Efforts to delelope farmer groups in playing their function in occordace with the direction of devoloping farme groups as their functoin. The high and law development of farmer group is influenced by the amount of group function given and the members perceptions of farmer group. This research was conducted to see members perception of the function of farmer group in law rice farming. This research was carried out in the Syamtalira Aron sub-district of north aceh regency in november 2018. This study uses a qualitative descriptive analysis with a scate of briquetes. The members perception of the function of farme group on wetland rice farming as a forum of cooperation with an index value of 76.31% with a good category. A container with a index value of 79.31% a good category. As a production unit with an index of 73.12% with catagor well.Therefore it can be concluded that in general farmers perception of the function of farmer group in lawland farming are categorized as good.